2016
DOI: 10.1021/acs.jpcc.6b08588
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Cone Angle and Surface Charge Density on the Ion Current Rectification Behavior of a Conical Nanopore

Abstract: Due to its potential applications in biotechnology, ion current rectification (ICR) arising from the asymmetric nature of ion transport in a nanochannel has drawn the attention of researchers in various fields. Previous studies usually neglect the effects of osmotic and electroosmotic flows. In this study, a more general model taking account of these effects is adopted to describe the ICR behavior of a conical nanopore. The influences of the cone angle, surface charge density, and bulk salt concentration on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 59 publications
5
79
1
Order By: Relevance
“…considered the effects of permeation and electro‐osmotic flow in the study to describe the ICR behaviour of tapered nanopores as shown in Fig. . The results showed that the cone angle, surface charge density and body salt concentration have an important influence on the local maximum in the ICR ratio.…”
Section: Applications Of Ion Transport Based On Icpmentioning
confidence: 99%
See 1 more Smart Citation
“…considered the effects of permeation and electro‐osmotic flow in the study to describe the ICR behaviour of tapered nanopores as shown in Fig. . The results showed that the cone angle, surface charge density and body salt concentration have an important influence on the local maximum in the ICR ratio.…”
Section: Applications Of Ion Transport Based On Icpmentioning
confidence: 99%
“…The variation law of ion current rectification (ICR) ratio which varies (a) with surface charge density and half cone angle, (b) with different half cone angle and (c) different charge density.…”
Section: Applications Of Ion Transport Based On Icpmentioning
confidence: 99%
“…Through many experimental and theoretical studies conducted in the last decades, it has been concluded that the ICR phenomenon of nanochannels/nanopores can be attributed to their asymmetric characteristics. These include, for instance, geometry [20–28], surface charge [29, 30], chemical composition [31, 32], wettability [33], and external applied fields such as pH gradient [34], electrolyte concentration gradient [35], and pressure gradient [36]. Among these, geometry‐induced ICR draws much attention because the associated nanochannel fabrication methods are convenient and controllable.…”
Section: Introductionmentioning
confidence: 99%
“…Through these methods, various types of nanochannels have been fabricated such as cylindrical [27], conical [22], hourglass‐shaped [26], cigar‐shaped [20], bullet‐shaped [25], dumbbell‐shaped [21], and funnel‐shaped nanochannels [23]. The ICR behavior of an asymmetric nanochannel can be influenced by factors including ionic species [40], ion concentration [35, 41], applied electric potential [40], pH [42, 43], temperature [44], and nanochannel length and its opening radii [24, 45, 46]. The cone angle [24] and the ratio of cylindrical segment/conical segment [23] are important to conical and funnel‐shaped nanochannels, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation